The Impact of Experience on Kibbutz Farming - Barkai, Haim; Levhari, David (The Review of Economics and Statistics, 1973)
T is an accepted proposition that there is a positive association between efficiency and experience in production. Yet, until quite recently, only industrial engineers tried to estimate and evaluate the contribution of experience to productivity, while economists have on the whole neglected this aspect of production. The growing interest in growth and the search for factors which can help to explain quantitatively the growth of production over and above the growth of the conventionally identified inputs have led economists to reconsider the problem. Arrow's pioneering article on the subject suggested that learning, which may be identified with cumulated experience, contributes to the growth of productivity.' In contrast to the engineer's approach, which usually concentrates on the effect of experience on efficiency in specific processes, the economist's approach is more general. Learning is not exclusively attributed to the individuals who make up a firm's labor force or to specific processes, though both are considered to be integral elements of the process. Rather, it is ascribed to the production unit as a multidimensional entity. It is therefore the modus operandi of the firm in each of its many facets entrepreneurial ability, technical expertise, the know-how of its labor force, layout, buying and selling, human relations, lines of command, all of them subject to continuous change which is the best testing ground of the empirical significance of the learning hypothesis. Since the acquisition of experience requires time, time or a proxy for it, such as cumulated investment and cumulated output, must obviously appear as an explicit variable in an empirical test of the hypothesis. Productionfunction analysis based on time series is therefore an obvious way of studying the quantitative effect of learning. Arrow's reference to the Swedish Horndal firm is a case in point.2 However, it is only rarely possible to find a similar example. This means that although empirical testing of the learning hypothesis can be carried out on the basis of time-series data,3 it strains the theoretical framework of the analysis. The use of cross-section data in estimating the contribution of experience to productivity is therefore an obvious alternative. Since the input and output figures necessarily refer to different firms, this way of tackling the problem is also constrained by the necessity of assuming that, except for random differences, the technologies applied by the firms concerned are identical. The requirement of intra-firm technological identity, or to put it more mildly, the similarityof-technology condition, can, in practice, be approximated under certain conditions. For example, a good approximation to the identical technology constraint can be obtained within a narrowly defined branch and for a group of firms located in a relatively small area, which maintain strong personal contact between managements so as to facilitate the inter-firm flow of information and whose labor forces are similar in background, attitude, and know-how. If the firms in such a group differ in their acquired experiences, and if these differences can be easily measured in terms of simple units, such a group may be a satisfactory testing ground for the learning hypothesis. These conditions obtain in the case of kibbutzim in Israel. They form a tightly organized group of collectives, relatively homogeneous in manpower, which has established effiReceived for publication December 6, 1971. Revision accepted for publication July 10, 1972. * This article makes use of data prepared for a comprehensive study on the Israeli kibbutz economy currently in preparation at the Falk Institute for Economic Research in Israel, and financed by the Falk Institute and the Twentieth Century Fund. The authors are indebted to Yoram Levin for his help in the preparation of the quantitative skeleton of this article. 1See Kenneth J. Arrow (1962), pp. 155-174. 2Production methods in this firm do not appear to have changed for about 15 years; productivity, however, increased continuously. 'Shifts in the production function cannot be ruled out if the period studied is long. For shorter periods, for which this objection may have less force, the number of observations may be too small to allow for statistically significant results.